Multi-Objective Optimization Study on Production of AlSi10Mg Alloy by Laser Powder Bed Fusion - İnayet Burcu Toprak; Nafel Dogdu (Applied Sciences)
In additive manufacturing, production parameters play a critical role in the microstructure, mechanical properties, and surface quality of a product. The correct selection of these parameters is of great importance for the success of the production process. In this study, the aim was to improve product quality in the additive manufacturing of an AlSi10Mg alloy. The experiments were conducted using a full factorial design, with a constant layer thickness of 0.04 mm. The production parameters included two laser powers (200 and 275 W), two scanning speeds (800 and 1400 mm/s), and two hatch distances (0.08 and 0.14 mm). The performance properties of the produced parts were evaluated according to the relative density and surface roughness criteria. The TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method was used to optimize both relative density and surface roughness performances simultaneously. The results revealed that the most suitable production parameters for the additive manufacturing of the AlSi10Mg alloy were 275 W laser power, 0.14 mm hatch distance, and 800 mm/s scan speed.